Anti-Helicobacter pylori, cytotoxicity and catalytic activity of biosynthesized gold nanoparticles: Multifaceted application - Gopinath, Venkatraman; Priyadarshini, S.; MubarakAli, Davoodbasha; Loke, Mun Fai; Thajuddin, Nooruddin; Alharbi, Naiyf Sultan; Yadavalli, Tejabhiram; Alagiri, Mani; Vadivelu, Jamuna (Elsevier, 2019)
An unpretentious way to synthesize different sized gold nanoparticles (GNPs) using the dried fruit extract of Tribulus terrestris has been investigated. GNPs were formed due to the reduction of chloroauric acid (HAuCl4) treated with the T. terrestris fruit extract. Formation of GNPs was periodically characterized by UV–Vis spectroscopy. IR spectrum revealed that phytochemicals in the extract played a key role in GNPs synthesis and stability. An anisotropic structure of GNPs with average sizes of 7 nm (GNP7) and 55 nm (GNP55) uses 1 and 2 mM HAuCl4. The biogenic GNP showed a size dependent anti-Helicobacter pylori activity against multidrug resistant H. pylori strains. Furthermore, biogenic GNPs possess an excellent catalytic activity for the reduction of a toxic, p-nitroaniline to p-phenylenediamine as non-toxic by-product. Interestingly, In vitro cell viability of GNP7 and GNP55 on AGS cell lines showed no toxicity at the MIC of H. pylori. The biogenic GNP has excellent biocompatibility, anti-H. pylori and catalytic properties of multifaceted biomedical applications.